Where has all the money gone? Foreign aid and the quest for growth - Santanu Chatterjee; Paola Giuliano; Ilker Kaya (Institute for the Study of Labor (IZA), 2007)
This paper examines fungibility as a possible explanation for the missing link between foreign aid and economic growth. The composition of aid plays a crucial role in determining the composition of government spending and, consequently, the magnitude of fungibility and its impact on growth. Embedding fungibility as an equilibrium outcome in an endogenous growth framework, we show that the substitution away from domestic government investment is higher than from government consumption. This leads to a reduction in domestic productive public spending and completely offsets any positive impact that aid might have on growth. The main predictions of the model are tested using a panel dataset of 67 countries for 1972-2000. We find strong evidence of fungibility at the aggregate level: almost 70 percent of total aid is fungible in our sample. We also find that investment aid is more fungible than other categories of aid. In the presence of fungibility, there is no statistically significant relationship between foreign aid and economic growth.
Keywords: 330; Entwicklungshilfe; Entwicklungsfinanzierung; Öffentliche Ausgaben; Budgetrestriktion; Wirtschaftswachstum; Entwicklung; Entwicklungsländer; Welt